Spectrophotometric Determination of Ziprasidone in Pharmaceutical Formulations - G. Srinubabu; B. Sudha Rani; J. V. L. N. Seshagiri Rao (E-Journal of Chemistry)
A simple and reproducible spectrophotometric method has been developed for the determination of Ziprasidone hydrochloride monohydrate (ZPS) in bulk and in dosage forms. The method is based on the extraction of the drugs into organic layer of the dye TPooo in presence of 0.1 N hydrochloric acid and the absorbances were measured at 490 nm. Results indicate that the proposed method was simple, sensitive, accurate and reproducible.